Pengaruh Media Kartu Kata Bergambar Terhadap Kemampuan Membaca Permulaan Siswa Kelas I di SD Negeri 1 Mekarjaya (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effect of picture-word cards on the early reading skills of first-grade students at SD Negeri 1 Mekarjaya. The study employed a quantitative approach using a quasi-experimental method and a non-equivalent control group design. The sample consisted of 30 students, divided into an experimental group of 16 students and a control group of 14 students. Data were collected via pre-tests and post-tests and subsequently analyzed using descriptive statistics and the Mann-Whitney U test. The results showed that the experimental group's average early reading ability increased from 9.25 in the pre-test to 11.50 in the post-test, a difference of 2.25. Meanwhile, the control group improved from 9.36 to 11.79, a difference of 2.43. Although both groups showed improvement, the Mann-Whitney U test yielded a significance value (Sig.) of 0.933 (greater than 0.05), indicating no significant difference between the two groups. Thus, the use of picture-word cards has not demonstrated a significant effect on the early reading skills of first-grade students at SD Negeri 1 Mekarjaya.